Macrosystem Analysis of Programs and Strategies to Increase Underrepresented Populations in the Geosciences. Issue 4 (1st November 2017) - Wolfe, Benjamin A.; Riggs, Eric M.
ABSTRACT: Meeting the future demand for a qualified geoscience workforce will require efforts to increase recruitment, retention, and graduation of an increasingly diverse student body. Doing this successfully requires renewed attention to the needs and characteristics of underrepresented students, which include ethnic and cultural minorities, women, and students with disabilities. We synthesize the current literature on successful science, technology, engineering, and mathematics (STEM) diversity programs and programs in the geosciences specifically through the lens of educational macrosystems. Macrosystems are an element of an approach to analysis of educational systems and institutions that adopts a social–ecological model. Interacting subsystems of microsystems, mesosystems, macrosystems, and exosystems operate together to contribute to student success. STEM fields in general and geoscience in particular have benefited from recent research into microsystems, the student-centric, intrinsic aspects of success. The synthesis we present here is intended to add a new dimension to this body of literature, highlighting reports from successful STEM and geoscience-specific programs that have worked to strengthen macrosystems, which are extrinsic factors that surround students. These include peer support and faculty mentoring networks, institutional bridge programs, systemic pedagogy reforms, and purposeful work to improve campus climate, culture, and accountability for diversity. This synthesis is not comprehensive but rather aims to highlight and illustrate elements of selected successful programs. We conclude with general recommendations and observations intended to be helpful to the geosciences education community in directing future work to optimize macrosystems in support of diversifying the geosciences.